Odd Generalized Rayleigh- Exponential distribution Statistical Properties with Real Data Application - ِAli Monef (Kirkuk Journal of Science)
In this paper we offer a new distribution due to the most common problem for researchers is to determine a statistical model for analyzing lifetime data. There are many ways to add a scaling parameter or a shape parameter by generalizing the distributions. So  statistical model called the Generalized Rayleigh Exponential Distribution (OGRE) is presented. Some different properties of this distribution including moments, moment generating function, hazard function, survival function, ordered statistics and piecewise function are studied. Maximum likelihood estimators are used to estimate the parameters. In addition, the practical significance of )OGRE( is demonstrated by two real data sets and the results are compared with a set of other related distributions. simulation is also performed